Anemia and Vitamin B-12 and Folate Status in Women of Reproductive Age in Southern India: Estimating Population-Based Risk of Neural Tube Defects. Issue 5 (26th April 2021) - Finkelstein, Julia L; Fothergill, Amy; Johnson, Christina B; Guetterman, Heather M; Bose, Beena; Jabbar, Shameem; Zhang, Mindy; Pfeiffer, Christine M; Qi, Yan Ping; Rose, Charles E; Williams, Jennifer L; Bonam, Wesley; et al.
ABSTRACT: Background: Women of reproductive age (WRA) are a high-risk population for anemia and micronutrient deficiencies. However, there are few representative population-level data from India, which could help inform evidence-based recommendations and policy. Objective: To conduct a population-based biomarker survey of anemia and vitamin B-12 and folate status in WRA as part of a periconceptional surveillance program in southern India. Methods: Participants were WRA (15–40 y) who were not pregnant or lactating. Whole blood ( n  = 979) was analyzed for hemoglobin via a Coulter counter (Coulter HMX). Plasma, serum, and RBCs were processed and stored at −80°C or less until batch analysis. Vitamin B-12 concentrations were measured via chemiluminescence; RBC and serum folate concentrations were evaluated via microbiological assay. Anemia and severe anemia were defined as hemoglobin <12.0 g/dL and <8.0 g/dL, respectively. Vitamin B-12 deficiency and insufficiency were defined as total vitamin B-12 <148 pmol/L and <221 pmol/L, respectively. Folate deficiency and insufficiency were defined as RBC folate <305 nmol/L and <748 nmol/L. A previously developed Bayesian model was used to predict neural tube defect (NTD) prevalence per 10, 000 births. Results: A total of 41.5% of WRA had anemia and 3.0% had severe anemia. A total of 48.3% of WRA had vitamin B-12 deficiency and 74.3% had vitamin B-12 insufficiency. The prevalence of RBC folate deficiency was 7.6%, and 79.3% of WRA had RBC folate <748 nmol/L, the threshold for optimal NTD prevention. Predicted NTD prevalence per 10, 000 births based on RBC folate concentrations was 20.6 (95% uncertainty interval: 16.5–25.5). Conclusions: The substantial burden of anemia, vitamin B-12 deficiency, and RBC folate insufficiency in WRA in this setting suggests an opportunity for anemia and birth defects prevention. Findings will directly inform the development of a randomized trial for anemia and birth defects prevention in southern India. This study was registered at clinicaltrials.gov as NCT04048330.